Activity of novel insecticides against different life stages of whitefly (Bemisia tabaci) - KUMAR, VIJAY; JINDAL, VIKAS; KATARIA, S K; PATHANIA, MANDEEP (The Indian Journal of Agricultural Sciences, 2019)
Whitefly, Bemisia tabaci (Gennadius), in North Cotton Growing Zone of India adversely affect cotton yield. Both the nymphal and adult stages of whitefly cause damage by sucking the sap from leaf tissue and honey dew secretion. In this study, the efficacy of new generation insecticides, viz. pyriproxyfen 10EC@1250 ml/ha, spiromesifen 22.9SC @500 ml/ha, flonicamid 50WG @200g/ha, and diafenthiuron 50WP @ 500g/ha were evaluated against different stages of whitefly under confined as well as field conditions in Bt cotton.The experiment conducted in screen house revealed significantly higher per cent reduction of whitefly nymphs in spiromesifen 22.9SC (49.36, 75.17) followed by pyriproxyfen 10EC (33.26, 75.07) in comparison to all other treatments after 5 and 7 days of spray, respectively. Under field conditions, pooled analysis of six experiments showed that flonicamid 50WP was more effective, being at par with pyriproxyfen 10EC, diafenthiuron 50WP, spiromesifen 22.9SC after 10 days of spray as compared to standard check, ethion 50EC and control against whitefly adults. It is concluded that pyriproxyfen10EC and spiromesifen 22.9SC have good nymphicidal action while flonicamid 50WP and diafenthiuron 50WP have adulticidal action.Therefore, for its effective management, these novel insecticides can be rotated alternatively depending upon the stage of pest dominating in the cotton field.